Thermogravimetric analysis of cellulose insulation and determination of activation energy of its thermo‐oxidation using non‐isothermal, model‐free methods. (6th August 2014) - Rantuch, Peter; Balog, Karol
<x xml:space="preserve">Abstract</x> The aim of the work was to determine the effect of heating rate on initial decomposition temperature and phases of thermal decomposition of cellulose insulation. The activation energy of thermo‐oxidation of insulation was also determined. Individual samples were heated in the air flow in the thermal range of 100°C to 500°C at rates from 1.9°C min−1 to 20.1°C min−1. The initial temperatures of thermal decomposition ranged from 220°C to 320°C, depending on the heating rate. Three regions of thermal decomposition were observed. The maximum rates of mass loss were measured at the temperatures between 288°C and 362°C. The activation energies, which achieved average values between 75 and 80.7 kJ mol−1, were calculated from the obtained results by non‐isothermal, model‐free methods. Copyright © 2014 John Wiley & Sons, Ltd.